Machine Learning-Assisted Screening of Herbal Medicine Extracts as Vaccine Adjuvants - Hioki, Kou; Hayashi, Tomoya; Natsume-Kitatani, Yayoi; Kobiyama, Kouji; Temizoz, Burcu; Negishi, Hideo; Kawakami, Hitomi; Fuchino, Hiroyuki; Kuroda, Etsushi; Coban, Cevayir; Kawahara, Nobuo; Ishii, Ken J. (Frontiers in Immunology, 2022)
Adjuvants are important vaccine components, composed of a variety of chemical and biological materials that enhance the vaccine antigen-specific immune responses by stimulating the innate immune cells in both direct and indirect manners to produce a variety cytokines, chemokines and growth factors. It hast been developed by empirical methods for the last decades, and considered difficult to choose a single screening method for an ideal vaccine adjuvant, due to their diverse biochemical characteristic, complex mechanisms of, and species specificity for their adjuvanticity. We therefore established a robust adjuvant screening strategy by combining multiparametric analysis of adjuvanticity in vivo and immunological profiles in vitro (such as cytokines, chemokines, and growth factor secretion) of various library compounds derived from hot-water extracts of herbal medicines, together with their diverse distribution of nano-sized physical particle properties with a machine learning algorithm. By combining multiparametric analysis with a machine learning algorithm such as rCCA, sparse-PLS and DIABLO, we identified that human G-CSF and mouse RANTES, produced upon adjuvant stimulation in vitro, are the most robust biological parameters that can predict the adjuvanticity of various library compounds. Notably, we revealed a certain nano-sized particle population that functioned as an independent negative parameter to adjuvanticity. Finally, we proved that the two-step strategy pairing the negative and positive parameters significantly improved the efficacy of screening and a screening strategy applying principal component analysis using the identified parameters. These novel parameters we identified for adjuvant screening by machine learning with multiple biological and physical parameters may provide new insights into the future development of effective and safe adjuvants for human use.